Without making a song and dance about it… - Williams, Katherine (Jazz Research Journal, 2022)
This story can be read in three ways. The Story is a fictional day in the life of a female jazz guitarist. The Endnotes tell another story, a referenced timeline of discrimination and sexism against female and minority musicians. You could read The Story by itself. You could read The Endnotes by themselves—taken together, they form a prose story of some of the barriers faced by musicians outside the cishet male narrative. Thirdly, you could refer to each endnote as it appears in the story. This method will be a disjointed reading experience, but perhaps best represents the doublethink necessary from people outside the dominant demography in today’s society.